Improve production of microbial cellulose by acetobacter xylinum with addition of microparticles in synthetic and complex media under shaking culture conditions - Muhamad, Ida Idayu; Abdul Talib, Siti Zalita; Abdullah, M. Zailani; Mahat, M. Khairizal; Ho, Kek Sian (2005)
Acetobacter xylinum is a type of bacteria that can synthesize cellulose when grown in a synthetic and complex medium containing glucose. The effect of microbial cellulose productivity by adding insoluble microparticles (sea sand) to submerged, shaken Acetobacter xylinum culture run at 100, 120, 160 and 200 rpm was investigated. The optimal conditions for this culture were at pH 5.0, 300Â°C and 5 days incubation. Both of synthetic and complex media (sugarcane juice) were used in this study for comparisons. The result shows that cellulose production in the microparticle-added media was higher than in the control media at shaking speed 120 rpm, 160rpm and 200 rpm. It is also found that production of cellulose in the complex media was higher than in the synthetic media and with lower water content. Furthermore the highest yield of cellulose was obtained from using shaking speed at 120 rpm in all cases. Keywords: Acetobacter xylinum, microbial cellulose, microparticles, synthetic and complex media.